Role of the Soluble Receptor for Advanced Glycation End Products (sRAGE) as a Prognostic Factor for Mortality in Hemodialysis and Peritoneal Dialysis Patients - Dozio, Elena; Ambrogi, Federico; de Cal, Massimo; Vianello, Elena; Ronco, Claudio; Corsi Romanelli, Massimiliano M. (Mediators of Inflammation, 2018)
End-stage renal disease patients on dialysis (CKD-G5D) have a high mortality rate due to cardiovascular diseases (CVD). In these patients, inflammation, oxidative stress, and uremia increase the production of glycation products (AGEs) which in turn accelerate CVD onset and progression. Recently, attention has been given to the soluble receptor for AGEs (sRAGE) as a marker of inflammation, oxidative stress, atherosclerosis, and heart failure in CKD-G5D. However, its association with patient outcomes is still under debate. Our aim is to explore whether sRAGE may be a predictor of mortality in CKD-G5D. We studied 123 CKD-G5D for 24 months. Of these patients, 56 were on hemodialysis (HD) and 67 on peritoneal dialysis (PD). Demographic, anthropometric, biochemical, and clinical data were recorded. sRAGE was quantified by enzyme-linked immunosorbent assay. sRAGE was a predictor of mortality at 2-year follow-up. Each increase of 100 pg/mL in sRAGE levels was associated with an approximately 7% increased risk of mortality. Furthermore, in the entire study group, as well as in PD and HD patient subgroups, sRAGE was positively correlated with brain natriuretic peptide (BNP) levels. Mortality rates as well as sRAGE levels in patients who died did not differ between PD and HD patients. In conclusion, the positive association observed with BNP levels suggests a role for sRAGE as a prognostic factor for mortality in CKD-G5D patients displaying an active process of cardiac remodeling.